METODE KOMPUTASI MURAH UNTUK SINKRONISASI FASA OPTIK PADA OPTICAL BEAMFORMING NETWORKS - Herminarto Nugroho; Wahyu Kunto Wibowo; Aulia Rahma Annisa (JURNAL TEKNOLOGIA, 2019)
Optical Beamforming Networks (OBFNs) is used to optimized the received signal power in airplane-satellite communication by controlling the signal beams towards the desired direction. The control of these OBFNs is a difficult and very complex nonlinear problem. The complexity of OBFN can be reduced by lowering the bandwidth of the modulated optical signals at its inputs. It can be achieved by performing optical single-sideband suppressed-carrier (SSB-SC) modulation. However, there is potential problem due to the fact that the phase relation between the optical carrier and the remaining sideband is lost when the group delay response is only optimized for the sideband frequency range. Optical phase synchronization is used to correct this issue by adding extra phase shifters. However, there is not any simple yet effective method to determine the value of the extra phase shifters needed for a certain OBFN. This paper propose a simple and computationally cheap feedback approximation approach to solve this problem.